The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3847/1538-4357/ac972b
|View full text |Cite
|
Sign up to set email alerts
|

A Short Gamma-Ray Burst from a Protomagnetar Remnant

Abstract: The contemporaneous detection of gravitational waves and gamma rays from GW170817/GRB 170817A, followed by kilonova emission a day after, confirmed compact binary neutron star mergers as progenitors of short-duration gamma-ray bursts (GRBs) and cosmic sources of heavy r-process nuclei. However, the nature (and life span) of the merger remnant and the energy reservoir powering these bright gamma-ray flashes remains debated, while the first minutes after the merger are unexplored at optical wavelengths. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 150 publications
0
7
0
Order By: Relevance
“…The resulting thermal emission would be significantly enhanced and brighter than transients purely powered by r-process nucleosynthesis. This model, applied to GRB180618A [167], GRB050724A, and GRB061006A [162], can reproduce their luminous optical emission for reasonable values of the magnetic field, B ≈ 5 × 10 15 G, and initial spin period, P ≈ 3-5 ms. The extreme luminosities implied by some magnetar-powered models can be constrained with wide-field optical surveys [57].…”
Section: Kilonovae Associated With Hybrid Long Grbsmentioning
confidence: 92%
See 1 more Smart Citation
“…The resulting thermal emission would be significantly enhanced and brighter than transients purely powered by r-process nucleosynthesis. This model, applied to GRB180618A [167], GRB050724A, and GRB061006A [162], can reproduce their luminous optical emission for reasonable values of the magnetic field, B ≈ 5 × 10 15 G, and initial spin period, P ≈ 3-5 ms. The extreme luminosities implied by some magnetar-powered models can be constrained with wide-field optical surveys [57].…”
Section: Kilonovae Associated With Hybrid Long Grbsmentioning
confidence: 92%
“…All the bursts in Table 2 have an X-ray afterglow, and only 2 lack an optical counterpart. Swift/UVOT detections were reported for GRB180618A [167] and for the three closest events, namely GRB060505, GRB060614, and GRB211211A. In the latter two cases, the detection in all 6 UVOT filters (v, b, u, uvw1, uvm2, uvw2) helped constrain the GRB distance scale (z ≲ 1.5) directly from the afterglow data, and ruled out high values of dust extinction along the line of sight [42,172].…”
Section: Kilonovae Associated With Hybrid Long Grbsmentioning
confidence: 98%
“…See Strang et al (2021), however, for an alternative study in which radiation driven from a millisecond magnetar can account for short GRB X-ray afterglows. See Dall'Osso and Stella (2022) for a recent brief review of millisecond magnetars, including evidence of their serving as central engines to create GRBs, and see Jordana-Mitjans et al (2022) for evidence of a protomagnetar remnant in the aftermath of GRB 180618A.…”
Section: Magnetic Dipole (N = 3)mentioning
confidence: 99%
“…Nevertheless, it was pointed out by Ibrahim et al (2008) as a potential event from an emerging class of short bursts with EE and as a possible GRB with EE. Moreover, the EE of GRB 180618A (Fong et al 2022;Jordana-Mitjans et al 2022;O'Connor et al 2022), GRB 170728B (Fong et al 2022;O'Connor et al 2022), GRB 180805B (Fong et al 2022;O'Connor et al 2022), and GRB 200219A was suggested in the Gamma-ray Coordinates Network / Transient Astronomy Network (GCN/TAN)circulars.…”
Section: Identification Of Ee Grb Candidatesmentioning
confidence: 99%